Contemporary aspects of the promotion of democracy by the European Court of Human Rights - Mowbray, Alastair (Wolters Kluwer, 2014)
This article examines the recent jurisprudence of the European Court of Human Rights concerning States obligations in regard to the maintenance and enhancement of democratic political activities within their societies. A selection of leading cases involving freedom of expression, freedom of association and free elections are analysed. These encompass controversial issues such as symbolic protests, the dissolution of non-governmental organizations and the restriction of voting rights applied to particular groups. Conclusions are drawn regarding how the contemporary case-law has built upon the foundations established by the original Court. Areas of uncertainty within the jurisprudence are identified together with case-law where the Court has exceeded its legitimate interpretative function. The Court's jurisprudence is also linked to debates within the philosophical world and amongst public international lawyers.